2004
DOI: 10.1196/annals.1320.007
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of l‐Carnitine and Propionyl‐l‐carnitine on Cardiovascular Diseases: A Review

Abstract: Several experimental studies have shown that levocarnitine reduces myocardial injury after ischemia and reperfusion by counteracting the toxic effect of high levels of free fatty acids, which occur in ischemia, and by improving carbohydrate metabolism. In addition to increasing the rate of fatty acid transport into mitochondria, levocarnitine reduces the intramitochondrial ratio of acetyl-CoA to free CoA, thus stimulating the activity of pyruvate dehydrogenase and increasing the oxidation of pyruvate. Suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
170
1
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(192 citation statements)
references
References 57 publications
2
170
1
14
Order By: Relevance
“…This was probably due to less damage having occurred from oxygen-free radicals. In previous studies, CDDP has been found to have an antiperoxidative effect on several tissues, such as the liver, kidney, and lens [35][36][37]. GSH is the most important molecule for maintaining cell integrity and participation in cell metabolism [38].…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to less damage having occurred from oxygen-free radicals. In previous studies, CDDP has been found to have an antiperoxidative effect on several tissues, such as the liver, kidney, and lens [35][36][37]. GSH is the most important molecule for maintaining cell integrity and participation in cell metabolism [38].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well known roles of carnitine, several studies suggest that carnitine is involved in a multitude of other processes, for instance sperm quality assurance, immune responses or myocardial integrity and function, explaining the large interest for carnitine and OCTN2 [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving about 2500 patients with coronary artery disease (CAD) treated with L-Car for a year also showed a reduced incidence of angina, a decreased need of cardiac drugs and a greater effort tolerance (Naguib, 2005). Placebo-controlled studies performed in patients with stable chronic effort angina suggest that L-Car given acutely (40 mg/kg, iv) or chronically (1-3 g daily for a month) improves exercise capacity and the electrocardiographic manifestations of ischemia (Ferrari et al, 2004). L-Car does not have hemodynamic effects in healthy volunteers or patients with CAD.…”
Section: Uses Of L-car In Cardiovascular Health and Diseasesmentioning
confidence: 99%
“…L-Car does not have hemodynamic effects in healthy volunteers or patients with CAD. However, an improvement of individual maximal aerobic power is demonstrated in healthy subjects and athletes after chronic treatment with L-Car (4 g daily over a period of 2 weeks) (Ferrari et al, 2004). In a randomized, double-blind, placebo controlled, multicenter study called the Levocarnitine Ecocardiografia Digitalizzata Infarto Miocardico (CEDIM) trial was performed to evaluate the effects of L-Car administration on long-term left ventricular dilatation in patients with AMI.…”
Section: Uses Of L-car In Cardiovascular Health and Diseasesmentioning
confidence: 99%